O sistema de avaliação da educação básica dos anos iniciais do ensino fundamental e indicadores de qualidade na gestão educacional/escolar em escolas municipais de Santa Maria – RS - Dutra, Marília Henn (2022)
This research constitutes the final level of the Master degree in Education, in the research field “Scholar practices and public policies” of the Postgraduate Program in Education of Federal University of Santa Maria. The study aimed to comprehend how the quality indices emerging on the System of Basic Education Assessment of the elementary school repercutes on the Municipal Secretary of Education’s (SMED) action planning and on scholar management. The specific objectives has been to comprehend the actions from SMED and assessment system on the work of Elementary school teachers; to identify SMED’s planning actions from the assessment indices; and to analyze the indices’ repercussions on the management actions of municipal schools. As theoretical support has been used authors such as Willmott (1992), Lück (2009), Ball (2005 e 2010), Libâneo; Oliveira; Toschi (2012), among others. The research was realized in public schools from Santa Maria, which had participated and had shown its results related to elementary school on the last five editions of SAEB. It was characterized as a qualitative research and the method for production data was semi-structured interviews with a teacher and a manager of each school, and also a manager from SMED. The state of knowledge also helped thematic understanding and deepening. This way, it has been possible to comprehend that control and performativity technologies as part of reality lived by teachers and managers, as well run through pedagogical practices, which are changed and influenced to reach assessment indices.